PENGARUH SISTEM AKUNTANSI PEMERINTAHAN, SISTEM PENGENDALIAN INTERN DAN GOOD GOVERNANCE TERHADAP KUALITAS LAPORAN KEUANGAN: (Studi Pada Satuan Kerja Perangkat Daerah Kabupaten Majalengka) - Robi Maulana (Program Studi Akuntansi Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2021)
This study aims to determine how the influence of the government accounting system on the quality of financial reports, the influence of the internal control system on the quality of financial reports, the effect of good governance on the quality of financial reports, and the effect of the government accounting system, internal control system and good governance simultaneously on the quality of financial reports. . The object of this research is the Regional Work Unit of Majalengka Regency. This research uses descriptive analysis method and verification analysis method with data collection techniques using purposive sampling technique in which the sample used is determined based on criteria. Respondents in this study were the Head of Service, Secretary / General Affairs, and treasurer / financial management division at the Work Unit of Majalengka Regency, totaling 64 people. In this study, there are independent variables, namely the government accounting system, internal control system, and good governance, and the dependent variable is the quality of financial reports. The data analysis techniques used were correlation coefficient analysis, determination coefficient analysis, and hypothesis testing (t test and f test). Based on the results of this study it can be concluded that the government accounting system affects the quality of financial reports, the internal control system affects the quality of financial reports, good governance affects the quality of financial reports, and the government accounting system, internal control system and good governance simultaneously affect the quality of reports. finance..